Development and Validation of Sport Law Knowledge Test - Erhan Devrilmez; Ekrem Yasin Tabak; Selahattin Akpınar; Tekin Çolakoğlu; Alparslan Aziz Tunç; Oruç Ali Uğur (Pamukkale Spor Bilimleri Dergisi)
This study aims to develop a valid and reliable Sport Law Knowledge Test for preservice sport management students. The test was prepared by a panel including two professors having expertise on curriculum development, two university instructors lecturing sport law course and a Turkish language expert. Panel discussed and prepared 25 multiple-choice questions. Participants were 205 (122 male and 83 female) preservice sport management students who had successfully completed sport law course. Rasch modeling was used to evaluate the validity and reliability of the Sport Law Knowledge Test. Results showed that all test items demonstrated high internal consistency and reliability for both test items and person attended this study. The wright map showed that items demonstrated the cumulative norm. Overall analysis showed good evidence to support the validity and reliability of Sport Law Knowledge Test. Developed test can be used for measuring sport law knowledge level of preservice sport management students.